Termos de parentesco em Apurinã e em Paumari: contatos linguísticos na região do município de Lábrea-AM - SILVA, Rayssa Rodrigues da (Universidade Federal do Pará, 2022)
The present work has as objective the examination of the kinship terminology in the Apurinã (Aruák) language, and its comparison with the kinship system and terminology in the Paumari (Aruá) language, in order to verify what both systems and terminologies reveal about linguistic contact in the region of Lábrea-AM. This investigation will also occur through a brief comparison of the study objects with other languages spoken in the same region. Throughout the paper, we will present the lexical items that compose both terminologies; which in Apurinã corresponds to the Iroquois kinship model, while in Paumari it is similar to the Dravidian terminology pattern proposed by Dumont (1983). We will also discuss the correlation of terms to the kinship system of these peoples, and demonstrate the morphological characteristics of this semantic group. To carry out this research, we revisited previous anthropological works (there are no works by linguists) on the Paumari people, such as Bonilla (2007) and Florido (2008); linguistic works, such as Facundes (2000) and Freitas (2017), and anthropological works like Schiel (2004) on the Apurinã people and their language; we also use the theoretical-methodological tools of descriptive linguistics, anthropological linguistics (Durantti 1977; Foley 1997) and anthropology (Lévi-Strauss 1982; Ghasarian 1999). The corpus was collected during field research conducted by the author herself.